Submaximal exercise responses in tetraplegic, paraplegic and non spinal cord injured elite wheelchair athletes - Leicht, C. A.; Bishop, N. C.; Goosey-Tolfrey, V. L. (Scandinavian Journal of Medicine & Science in Sports, 2012)
It remains unclear whether similar exercise prescription, based on physiological markers, can be applied to subgroups of wheelchair athletes with different disabilities. Therefore, 25 wheelchair athletes, divided into three subgroups [eight tetraplegic (TETRA), nine paraplegic (PARA) and eight non spinal cord injured (NON-SCI)], performed an exercise test consisting of incremental submaximal stages, covering a range from 40% to 80% peak oxygen uptake (%VO2peak). Oxygen uptake (V?O2), heart rate (HR), blood lactate concentration (BLa) and rating of perceived exertion (RPE) were obtained for each stage. Expressed as a function of BLa, no differences were found between subgroups with respect to %V?O2peak (group mean ± SD: 1.0 mmol/L: 53.9 ± 9.9%; 2.0 mmol/L: 70.7 ± 7.5%; 3.0 mmol/L: 78.5 ± 7.7%) and RPE [group mean (lower and upper quartile): 1.0 mmol/L: 10.8 (9.9, 12.2); 2.0 mmol/L: 13.6 (12.7, 14.3); 3.0 mmol/L: 14.9 (13.7, 16.5)]. Furthermore, no differences were found in the coefficient of determination (R2) of the HR-VO2 relationship in any of the subgroups (TETRA: 0.90 ± 0.12; PARA: 0.97 ± 0.02; NON-SCI: 0.96 ± 0.04). These results suggest that exercise prescription using measurements of VO2, BLa or RPE can be based on the same recommendations in all the subgroups studied. This finding has added value for TETRA athletes, as it offers alternatives to HR monitoring.